2010
DOI: 10.1590/s0104-56872010000400027
|View full text |Cite
|
Sign up to set email alerts
|

Transtorno do processamento auditivo (central) em indivíduos com e sem dislexia

Abstract: Subjects from the dyslexic group presented different patterns of (central) auditory processing disorder, with greater alteration in the tests that evaluate the temporal processing when compared to the tests that evaluate other auditory abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
0
17
0
3
Order By: Relevance
“…It is observed that the Musiek test showed statistical significance as the most difficult test, even for subjects without complaint or alteration of AP. In studies of temporal ordering, in recent years, the most used test was the Musiek test (6,23,26,27) . This result was expected, since one of the hypotheses for Musiek test for being considered the most difficult is the fact that it is constituted of stimuli that present small differences between frequency or duration stimuli, which make it a tough test for the differentiation of the features of tones.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that the Musiek test showed statistical significance as the most difficult test, even for subjects without complaint or alteration of AP. In studies of temporal ordering, in recent years, the most used test was the Musiek test (6,23,26,27) . This result was expected, since one of the hypotheses for Musiek test for being considered the most difficult is the fact that it is constituted of stimuli that present small differences between frequency or duration stimuli, which make it a tough test for the differentiation of the features of tones.…”
Section: Discussionmentioning
confidence: 99%
“…In students who presented alterations in WPRCT, it was also found the inadequacy of the simple temporal ordering ability, which is related to the ability to recognize, identify and order acoustic stimuli during a given period, according to the order in which they were presented (27) . Other studies (27)(28)(29) have verified the association between reading and temporal auditory processing. Since this auditory ability is essential for speech and language comprehension, its inadequacy may derive in orthographic difficulties and hindrance in the coding/decoding of both words and phrases (27,29) .…”
Section: Discussionmentioning
confidence: 87%
“…There was an agreement about the poor performance, in the evaluation of the auditory processing, of children with reading/writing disorders and dyslexia when compared to children without disorders, especially in temporal processing skills 15,[31][32][33][34][35][36][37] .…”
Section: Rgdtmentioning
confidence: 99%